Usage of mobile applications in diabetes management: a review - Nur Suraiya Abu Hassan Shaari; Zahara Abdul Manaf; Nazlena Mohamad Ali; Suzana Shahar; Nor Azlin Mohamed Ismail (Penerbit Universiti Kebangsaan Malaysia, 2016)
Peer-reviewed articles on the usage of mobile applications in the management of diabetes were reviewed. Studies using mobile device applications for diabetes interventions published between January 2007 and March 2013 were included in this review. Studies related to the developmental processes of the mobile applications were excluded. The characteristics of these studies and the outcomes of the methods used in the management of diabetes were gathered. We retrieved a total of 372 articles from ACM Digital library, PubMed and Proquest Medical Library. After applying the inclusion and exclusion criteria, 8 articles were eligible for further review. Most of the studies included in this review showed the effectiveness of mobile applications in diabetes management. Their major contribution comes from feedback functions of the systems that assist participants in the self-monitoring of their blood glucose and dietary intake. However, the majority of the studies showed the limited use of the mobile phone as a tool to input information into systems which would in turn convey a reminder message to the patient. In conclusion, with its features of portability and convenience, mobile application used in the management of diabetes has the potential to improve glycaemic control, resulting in significant clinical and financial benefits.